Effects of inulin and lactic acid bacteria strains on aflatoxin M1 detoxification in yoghurt. (June 2019) - Sevim, Sumeyra; Topal, G. Gizem; Tengilimoglu-Metin, M. Merve; Sancak, Banu; Kizil, Mevlude
Abstract: The aim of this study was to determine the binding ability of three lactic acid bacteria strains (LABs) ( L. plantarum ATCC 10697, B. animalis ATCC 27672, and B. bifidum ATCC 35914) to aflatoxin M1 (AFM1) from contaminated yoghurt and phosphate-buffered saline (PBS) either alone or in binary combination for different periods of cold storage (one or ten days) and to investigate the effect of inulin supplementation at 4% concentration on the AFM1 binding ability of LABs. The AFM1 binding capacities of cultures varied, ranging between 49.8 ± 2.53% to 60.8 ± 3.58% and 49.5 ± 2.00% to 55.1 ± 1.67%; the best AFM1 binding was observed with yoghurt starter (YS) +  B. bifidum - B. animalis (60.8%) (p < 0.001) and YS +  L. plantarum - B. bifidum mixtures (55.1%) (p < 0.01) after one day and ten days cold storage periods, respectively. Inulin supplementation led to increased AFM1 binding capacity of YS +  B. bifidum (p < 0.01), YS +  B. animalis (p < 0.01), and YS +  L. plantarum - B. bifidum (p < 0.001) mixtures at the end of the one-day storage period. Furthermore, the binding capacity of YS +  B. bifidum - B. animalis, YS +  L. plantarum - B. bifidum, YS +  L. plantarum - B. animalis increased with statistical significance at the end of the ten-day storage period by inulin addition (p < 0.05, p < 0.001 and p < 0.001, respectively). The results of this study showed that the use of LABs and inulin in yoghurt manufacture might provide an effective method for AFM1 detoxification and reducing the exposure. Highlights: Aflatoxin M1 binding capacity of three LAB strains and inulin supplementation were investigated. LAB strains reduced AFM1 levels in yoghurt. Inulin supplementation led to increase AFM1 binding capacity of LABs. Binding capacity of LABs to AFM1 was species-dependent.